Protestant Clerical Marriage Customs in 16th-17th-Century Hungary - Marianna BÁTORINÉ MISÁK (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2024)
In my study, I attempt to provide an insight into the marriage customs of preachers and pastors of the time. In many respects, the marriage customs of the Hungarian pastors did not follow the practice proposed by the Western Reformers, since the conditions in Hungary did not always allow for the application of this pattern. Thus, remarriage, multiple remarriages, but also a large age difference between husband and wife were not uncommon. There were practical reasons behind both. Due to the lack of sources, my research into domestic customs has encountered many obstacles and I could not aim for completeness in my work. Nevertheless, I tried to collect the most typical data from the surviving sources, which would give me a picture of the marriage customs of Hungarian Reformed clergymen and the characteristics and circumstances that shaped them.